2007
DOI: 10.1016/j.visres.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol slows interhemispheric transmission, increases the flash-lag effect, and prolongs masking: Evidence for a slowing of neural processing and transmission

Abstract: While the alcohol literature is extensive, relatively little addresses the relationship between physiological effects and behavioural changes. Using the visual system as a model, we examined alcohol's influence on neural temporal processing as a potential means for alcohol's effects. We did this by using tasks that provided a measure of processing speed: Poffenberger paradigm, flash-lag, and backward masking. After moderate alcohol, participants showed longer interhemispheric transmission times, larger flash-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
1
14
0
1
Order By: Relevance
“…Neurovision studies have reported behavioral changes related to ingestion of alcohol, for example: (i) changes in perception and detection of asymmetry of facial expressions in both men and women (Oinonen & Sterniczuk, 2007); (ii) change in luminance processing speed in photopic and scotopic levels (Khan & Timney, 2007;Puell & Barrio, 2008). Even with physiological and Psychophysics findings, it is not possible to identify an explanatory model of action of alcohol on sensory and behavioral mechanisms of vision.…”
Section: Introductionmentioning
confidence: 99%
“…Neurovision studies have reported behavioral changes related to ingestion of alcohol, for example: (i) changes in perception and detection of asymmetry of facial expressions in both men and women (Oinonen & Sterniczuk, 2007); (ii) change in luminance processing speed in photopic and scotopic levels (Khan & Timney, 2007;Puell & Barrio, 2008). Even with physiological and Psychophysics findings, it is not possible to identify an explanatory model of action of alcohol on sensory and behavioral mechanisms of vision.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the tests have been widely employed as indices of a range of key cognitive processes that have previously been shown to be sensitive to the effects of alcohol intoxication, such as speed of information processing [10], [11], [12], [13], [14], [15], [16], divided attention [17], [18], [19], [20], [21], [22], [23]; problem solving [24], [25], [26], [27], [28], [29], [30], working memory [31], [32], [33], [34], [35], [36], response inhibition and cognitive flexibility [37], [38], [39], [40], [41], [42], and psychomotor functioning [18], [43], [44], [45], [46].…”
Section: Introductionmentioning
confidence: 99%
“…Among those is the suggestion that the effects of alcohol intake may result from depressant effects on the inhibitory control mechanisms and the action of neurotransmitters and neuromodulators, more specifically, the dampening effect of alcohol on the GABAergic system (i.e., gamma-aminobutyric acid) (7-9). …”
Section: Introductionmentioning
confidence: 99%